2022
DOI: 10.1097/md.0000000000029653
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of acupuncture point stimulation for the prevention of postoperative sore throat: A meta-analysis

Abstract: Background: Enhanced recovery pathways can be further improved for postoperative sore throat (POST) that occurs after surgery under general anesthesia. Medications have shown some effectiveness in preventing POST, but acupuncture or related techniques with better safety and lower cost can be used as an alternative or adjuvant therapy to treat perioperative symptoms by stimulating acupuncture point (acupoint). Therefore, we aimed to conduct a meta-analysis to assess whether acupoint stimulation helps patients p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Some studies have shown that medications, such as dexamethasone, lidocaine, ketamine, and magnesium, are effective in preventing POST. [5][6][7][8][9] In addition, non-pharmacological methods for preventing POST have been introduced [2,10,11] ; however, POST cannot be completely avoided. Furthermore, the incidence of POST after thyroid surgery is higher than that after other surgeries, and is also significantly higher in females.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that medications, such as dexamethasone, lidocaine, ketamine, and magnesium, are effective in preventing POST. [5][6][7][8][9] In addition, non-pharmacological methods for preventing POST have been introduced [2,10,11] ; however, POST cannot be completely avoided. Furthermore, the incidence of POST after thyroid surgery is higher than that after other surgeries, and is also significantly higher in females.…”
Section: Introductionmentioning
confidence: 99%
“…Although POST is a minor complication, it reduces patient satisfaction and extends the hospital stay. [ 1 , 2 ] The incidence of POST ranges between 12.1% and 70%, depending on the study. [ 3 ] The etiology of POST involves damage to the airway mucosa due to endotracheal intubation under GA. [ 4 ] The symptoms of POST include pain, discomfort, hoarseness, and coughing.…”
Section: Introductionmentioning
confidence: 99%